1997
DOI: 10.1046/j.1365-3180.1997.d01-15.x
|View full text |Cite
|
Sign up to set email alerts
|

Dose response of weeds to methyl iodide and methyl bromide

Abstract: Summary Labonuory bioassay and field experiments were conducted to characterize the dose response of weeds to methyl iodide and methyl bromide as soil fumigants. The patterns in potency of both fumigants and in sensitivity of diffcretit weed species to the fumigants were distinguished with the use of logistic dose‐response models. Similar to its response to methyl hromide fumigation. Amaranthus retrofleus L. was the most sensitive to methyl iodide fumigation. Cyperus rotundtis L. was the least sensitive to met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 14 publications
2
37
1
Order By: Relevance
“…Herbicide labels generally do not distinguish among the three species, and most refer only to redroot pigweed. The soil fumigants methyl iodide and methyl bromide have been reported to be effective at controlling populations of A. retroflexus (Zhang et al 1997).…”
Section: Response To Herbicides and Other Chemicalsmentioning
confidence: 99%
“…Herbicide labels generally do not distinguish among the three species, and most refer only to redroot pigweed. The soil fumigants methyl iodide and methyl bromide have been reported to be effective at controlling populations of A. retroflexus (Zhang et al 1997).…”
Section: Response To Herbicides and Other Chemicalsmentioning
confidence: 99%
“…Donald and Tanaka (1993) also found that annual application of AC94377 at 3.4 kg ha -1 in a field trial in North Dakota reduced seed survival of shallowly buried (1.25 cm deep) wild mustard by 80% after 3 yr. Zhang et al (1997) compared the dose response of eight weed species to two soil fumigants in the laboratory and field and found that methyl iodide was 50% more potent than methyl bromide for inhibiting germination of S. arvensis.…”
Section: Response To Other Human Manipulationsmentioning
confidence: 99%
“…Between species, the effects of applied herbicides were severe on P. oleracea control than A. retroflexus. Zhang et al (1997) demonstrated that photosynthetic inhibitors such as bentazon had an excellent performance on P. oleracea control. Fennimore and Rachuy (2005) reported that desmedipham/ phenmedipham and ethofumesate applications provided acceptable control of P. oleracea and A. retroflexus.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al (1997) reported that P. oleracea was resistant to PGR herbicides like 2,4-D and was tolerant to ALS inhibitor herbicides like imazethapyr. In contrast, clopyralid affected A. retroflexus at the same dosage (Fig.…”
Section: Discussionmentioning
confidence: 99%